Early Identification of Neuropathy in Patients with Diabetes Mellitus at RSUD Haji Adam Malik Medan Using the IpTT Method - Dewi Simanullang, Murni Sari; Rante Rupang, Ernita; Cellline Ayu Putri, Grace (Poltekkes Kemenkes Surakarta, 2024)
Background: Neuropathy is a condition of damage to the nerves of diabetes mellitus patients. Neuropathy can cause serious complications and can even cause amputation in sufferers. So it is necessary to do early detection of neuropathy, one of which is by using the IpTT method. Adam Malik General Hospital is one of the hospitals with the highest percentage of diabetes in Medan, with the cases reported by 1,323 people in 2020. This study aims to identify the incidence of neuropathy in DM patients at Haji Adam Malik General Hospital in Medan using the IpTT method. Methods: The research design used was a descriptive study with a cross-sectional approach with a population of 1470 inpatients. The sampling technique used accidental sampling with a sample of 52 respondents. The instrument used in this study is in the form of an observation sheet using the SOP of the IpTT Method. Results: The results of the study found that out of 52 respondents who had neuropathy, 5 respondents (10%) and 47 respondents (90%) did not experience neuropathy. Conclusion: It is hoped that from the results of this study, DM patients can prevent neuropathy by using the IpTT method.